Pertumbuhan Semai Pelita (Eucalyptus pellita) pada Berbagai Perlakuan Dosis Pupuk Dasar NPK dengan Sistem Hidroponik NFT: Growth of Pelita (Eucalyptus pellita) Seeds in Various Dose Treatments of NPK Basic Fertilizer with NFT Hydroponic System - Natashya, Ken Ghea; Andayani, Surodjo Taat; Yuslinawari, Yuslinawari (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
This reasearch aims to determine the dose of NPK basic fertilizer that is good for the growth of lamp seedlings. This study used an experiment with one treatment factor, namely the effect of NPK fertilizer doses arranged in a Complete Randomized Design (RAL). Treatment of 5 doses of NPK fertilizer, namely fertilizer dose 0 kg/m³, fertilizer dose 1.25 kg/m³, fertilizer dose 2.50 kg/m³, fertilizer dose 3.75 kg/m³ and fertilizer dose 5.00 kg/m³. The parameters used are seedling life percentage, seedling height, seedling diameter, number of leaves, primary root length and seedling sturdiness index. The results showed the percentage of seedling life for all treatments was 100%. The dose treatment of NPK fertilizer had a significant effect on seedling height, number of leaves and seedling diameter, while it had no significant effect on primary root length and seedling sturdiness index. The dose of NPK basic fertilizer 5 kg/m3 results in good growth of lamp seedlings. Semai pelita in all NPK fertilizer dosage treatments meet the seedling quality criteria in SNI 8420 : 2018. KEYWORDS: Eucalyptus pellita, NPK fertilizer, seedling growth